Implementation of Character Education at As Salam Malang Integrated Islamic Junior High School - Susilowati, Ambar Dyan; Mulyadi, Mulyadi; Esha, Muhammad In'am (AS-SABIQUN, 2025)
The implementation of character education at SMP Islam Terpadu As Salam Malang is guided by the school’s vision and mission: to be Qur’anic, excellent, and globally oriented. This study aims to describe the underlying concept of character education at the school, explain the strategies used in its implementation, and analyze the resulting outcomes. Utilizing a qualitative descriptive approach with a case study design, data were collected through interviews, observation, and documentation. The data were analyzed using the Miles, Huberman, and Saldana model, encompassing data condensation, data display, and conclusion drawing. Findings reveal that character education at SMP IT As Salam Malang is aligned with its vision and mission and is operationalized through three flagship programs: the Tahfidz Program, the Literacy Program, and the Pancasila Student Profile Strengthening Project (P5). Implementation strategies include comprehension, habituation, and role modeling. In the Tahfidz Program, these strategies are manifested through memorization, review (muraja’ah), and repetition (ziyadah). The Literacy Program incorporates daily reading of Sirah Nabawiyah and a “One Book One Week” initiative, supported by literacy logs and student recognition. The P5 Program emphasizes socialization of values and active student engagement in projects related to entrepreneurship, technology, and local wisdom. Outcomes indicate that the Tahfidz Program fosters discipline, responsibility, consistency (istiqamah), and Qur’an-inspired noble character; the Literacy Program promotes moral internalization through prophetic examples; and the P5 Program enhances cooperation, creativity, independence, and responsibility. These findings affirm that character education at SMP IT As Salam Malang is effectively integrated into daily school life through contextually relevant and spiritually grounded strategies.